Pengaruh Minat dan Lingkungan Belajar terhadap Kesiapan Belajar Dimediasi oleh Motivasi Belajar - Ade Setiawan; Dyah Sawitri; Endang Suswati (Ilmu Psikologi Universitas Yudharta Pasuruan)
Interest and learning environment are mediated by learning motivation is an important factor in increasing student learning readiness so that they affect the fluency in teaching and learning in educational institutions especially the Army Polytechnic. The results of this study indicate that: a) interest, learning environment, learning motivation, and readiness of learning in Army Polytechnic students are at a good level; b) interest directly has a positive and significant effect on learning motivation the Army Polytechnic students in Malang; c) the learning environment directly has a positive and significant effect on learning motivation the Army Polytechnic students in Malang; d) interest directly has a positive and significant effect on learning readiness of the Army Polytechnic students in Malang; e) the learning environment directly has a positive and significant effect on the readiness of learning the Army Polytechnic students in Malang; f) motivation to learn has influence directly, positively and significantly the readiness of learning for students of the Army Polytechnic in Malang; g) interest in mediating learning motivation indirectly has a positive effect on learning readiness the Army Polytechnic students in Malang; h) the learning environment with mediating learning motivation indirectly has a positive effect on the readiness of learning the Army Polytechnic students in Malang.